ORIGINAL ARTICLEPrediction of left ventricular remodelling in patients with acute myocardial infarction treated with primary percutaneous coronary intervention (prediction of remodelling) - Wita, Krystian; Filipecki, Artur; Węglarz, Przemysław; Szczogiel, Jan; Drzewiecka-Gerber, Agnieszka; Rybicka, Anna; Krauze, Jolanta; Wróbel, Wojciech; Nowak, Mariola; Konarska-Kuszewska, Ewa; Turski, Maciej; Tabor, Zbigniew; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2005)
Background: Fast and complete restoration of infarct related artery patency does not mean achievement of tissue perfusion, lack of which promotes remodelling and adversely affects left ventricular function. Aim of the study was to assess incidence of left ventricular remodelling, its prognostic value and factors predicting remodelling. Material and methods: Consecutive 90 patients (pts) presenting with first anterior myocardial infarction undergoing successful primary percutaneous coronary intervention (PCI) were prospectively enrolled. Angiographic parameters (Rentrop scale, myocardial blush grade (MBG), site of artery occlusion), electrocardiographic parameters (maximal ST segment elevation from single lead, sum of ST segment elevations and reduction of at least 50% of ST segment elevations 1 hour after PCI (S ST50%)), and biochemical parameters (maximal value of CK fraction of creatine kinase (CK-MB), troponin I, N-terminal proBNP (NT-proBNP)) were assessed. The following day echocardiographic assessment of left ventricular ejection fraction (LVEF), end-diastolic volume (LVEDV), and perfusion contrast imaging to determine regional perfusion score index (RPSI) were performed. Left ventricular remodelling was diagnosed based on echocardiography performed after 180 days. Results: Remodelling was found in 38 pts (42.2%). These patients suffered more frequently from serious adverse events: reinfarction or rehospitalization for heart failure (13 vs. 2, p 270 IU/l, NT-proBNP>920 pg/ml, maximal ST elevation >6mm and absence of? ST50% were significant predictors of remodelling. In multifactorial analysis only low RPSI, proximal LAD occlusion, maximal CKMB>270IU/l and lack of S ST50% remained significant predictors. Conclusions: Despite therapy according to current guidelines remodelling develops in significant proportion of pts with anterior MI. The present study supports high power of myocardial contrast echocardiography to predict remodelling among many established and well known electrocardiographic, angiographic, and biochemical indices.